Obciążenia obowiązkowe w strategii przedsiębiorstwa - Poszwa, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Taxes and other compulsory payments are strictly connected with running an enterprise. Thus, duties towards the national budget shall be included in the enterprise's strategy. The first task of the tax payer is heading to complete the tax duty. It is the condition of continuing the activity. The second issue is considering the taxes in the process of decision making including strategic decisions. Strategic aims and most of all their completion shall consider tax conditions of the enterprise activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 340-348